Electrochemical performance of spinel LiAlxMn2−xO4 prepared rapidly by glucose-assisted solid-state combustion synthesis. (October 2015) - Peng, Cancan; Huang, Jijun; Guo, Yujiao; Li, Qiling; Bai, Hongli; He, Yonghui; Su, Changwei; Guo, Junming
Abstract: Cathode materials of LiAlx Mn2−x O4 (x = 0, 0.02, 0.04, 0.08) with Fd3m space group were synthesized using glucose as the fuel by solid-state combustion synthesis at 500 °C in one hour. The effects of Al-doping on the crystal structures are systematically evaluated by X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy and scanning electron microscopy (SEM). The electrochemical performance of the cathode material LiAlx Mn2−x O4 was investigated by galvanostatic charge/discharge, cyclic voltammetry (CV) and electrochemical impedance spectra (EIS). Results show that doping Al significantly decreases the lattice parameter, changes the micromorphology and improves the electrochemical performance of LiMn2 O4 . This novel synthesis method will be benefit for the further improvement of the electrochemical performance of cathode materials in lithium cell. Highlights: Spinel LiAlx Mn2−x O4 was rapidly prepared by the solid-state combustion synthesis. The Al-doping samples with better electrochemical reversibility were obtained by a low-temperature method. Improved cycling performance is attributed to the enhanced crystal stability after doping Al.